Urban and Architectural continuity to Arab and Islamic heritage (Journal of Planner and Development, 2012)
This study try to discovering continuity in heritage, from its engaged with emotional side, the core of study is Islamic architectural, these architectural result still estate with time, due to role of it with Islam law, importance of continuity from finding real things of essential architects result The research reaching to concept of thoughtstaying, for Islamic heritage, as basic factor in continuity process by it is architecture. The mostly searches seeing imitation of figures as recently events, or as final result to stage conditions state, but we must remember the Islamic thinking as base stone to architecture results .